On the taxonomy and zoogeography of the Caucasian genus Pseudotyphlopasilia (Coleoptera: Staphylinidae: Aleocharinae). IV. Two new species and additional records from Northwest Georgia - Volker Assing (Contributions to Entomology)
Two field trips to Northwest Georgia conducted in 2021 yielded 29 specimens of the Caucasian genus Pseudotyphlopasilia Pace, 1983, most of them collected by soil-washing. The material belongs to five species, two of them described and three of them unnamed. Two of the unnamed species are described and illustrated: P. confusa spec. nov. (Racha: environs of Lailashi) and P. egrisica spec. nov. (Zemo Svaneti: Egrisi Range). One species remains unnamed for want of males. Additional records are provided for two previously described species, including Pseudotyphlopasilia coeca (Eppelsheim, 1878) (type species of the genus) of which only few and mostly old specimens were previously available. New illustrations are provided for P. coeca and P. acris Assing, 2021. The genus currently contains a total of twelve named species, all of them anophthalmous and micropterous, with eleven of them distributed in Georgia and one in the Russian West Caucasus. The distributions of five species are mapped.